Limitación de la movilidad articular de la mano y ateromatosis carotídea en diabéticos tipo 2 - Sisniegas-Vergara, César (2020)
Objetive: to determine the relationship between limited joint mobility (LJM) of the hand and the presence of atheroma plaques in the carotid arteries of patients with type 2 diabetes mellitus (DM2). Material and methods: 80 patients with DM2, in two groups (40 with LJM and 40 without LJM), between 40 and 80 years. LJM was diagnosed with a positive prayer maneuver. Using B-mode ultrasonography of the carotid arteries, atheromatous plaques were classified according to the Gray-Weale Scale. Results: There was no significant difference in age and sex between both groups. The LJM group had longer illness time. The values ​​of VLDL cholesterol, urea and creatinine were significantly higher in the LJM group. Both groups of patients had the same type of treatment for diabetes, high blood pressure and anti-dyslipidemic. LJM was associated with a greater number of atheromas. Type I, II and III carotid plaques were more frequent in patients with LJM. Conclusions: patients with DM2 and with LJM have a greater number of atheroma plaques in the carotid arteries than patients without LJM.